Effectiveness of Differentiated Learning Approaches to Enhance Students' Literacy and Numeracy - Siswanto, Deny Hadi; Syah, Arga Bagus Pratama Dyah Aan Firman; Yogyanto, Nurcahyo; Yarkasi, Yarkasi (Indonesian Journal of Educational Science and Technology, 2024)
This research aims to determine the effectiveness of the differentiated learning approach to improve student literacy and numeracy. The type of research used was quasi-experimental, with research subjects consisting of 60 students in class XI Multimedia A and XI Multimedia B at Muhammadiyah 1 Sleman Vocational High School. Data was collected through tests, observations and interviews. Data analysis techniques include validity and reliability tests for instrument tests as well as normality tests, homogeneity tests, and t-tests to determine the effectiveness of differentiated approaches to increase student literacy and numeracy, as well as Gain tests to determine the type of improvement. The research results showed that the data was normally distributed and homogeneous, so it was continued with the t-test. The t-test results are 0,000 < 0,05, meaning that the differentiated learning approach is effective in increasing student literacy and numeracy with an increase in the Gain test of 0.72 in the high category